Proses Penyidikan Terhadap Pelaku Tindak Pidana dengan Penyandang Tuna Rungu di Satuan Reserse Kriminal Polisi Resor Kota Bukittinggi - Fakhrul, Muhammad Fakhrul Hidayat; Yustrisia, Lola; Munandar, Syaiful (Universitas Medan Area, 2025)
The purpose of this study is to discuss the implementation of legal protection during the investigation process at the Bukittinggi City Police Resort for offenders with hearing disabilities and the challenges and efforts experienced by investigators in conducting investigations on offenders with disabilities. Law No. 19 of 2011 on the Ratification of the Convention on the Rights of Persons with Disabilities serves as a reference for protection for persons with disabilities. This research method is empirical juridical with a qualitative approach. Data were obtained through interviews and document studies conducted at the Criminal Investigation Unit of the Bukittinggi City Police Resort. The findings of the study show that there are slight differences in the investigation process between normal individuals and those with disabilities. Challenges faced by investigators include difficulty in communicating with the offender due to their being speech or hearing impaired. The efforts made by the investigators include calling in a special interpreter to assist in the investigation process. This research provides information on the legal protection for offenders with disabilities during the investigation process.